Comparing methods for assessing reliability uncertainty based on pass/fail data collected over time. Issue Volume 30:Issues 4(2018) (2nd October 2018) - Abes, Jeff I.; Hamada, Michael S.; Hills, Charles R.
ABSTRACT: In this article, we compare statistical methods for analyzing pass/fail data collected over time; some methods are traditional and one (the RADAR or Rationale for Assessing Degradation Arriving at Random) was recently developed. These methods are used to provide uncertainty bounds on reliability. We make observations about the methods' assumptions and properties. We illustrate the differences between two traditional methods, logistic regression and Weibull failure time analysis, and the RADAR method using a numerical example.